Studi Literatur: Dampak Metode Penggorengan Terhadap Kandungan Gizi Makanan Tradisonal Indonesia - Salwa Maulidia; Marthen Maju Panjaitan; Fatma Tresno Ingtyas; Laurena Ginting (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Frying is one of the most common food processing techniques used in preparing traditional Indonesian dishes. This process not only enhances flavor, texture, and color but also has the potential to reduce nutritional quality due to high temperature exposure, oil oxidation, and repeated use of cooking oil. This study is a literature review aimed at examining the effects of various frying methods—such as deep frying, pan frying, repeated oil frying, and vacuum frying—on the nutritional content of traditional Indonesian foods. Data were collected from national scientific journals published between 2018 and 2024 that discuss frying processes and nutritional values. The results show that temperature and frying duration significantly influence the levels of moisture, fat, protein, and vitamins in food materials. The repeated use of oil increases free fatty acids (FFA) and peroxide values, indicating deterioration of oil quality and the formation of harmful oxidative compounds. A comparison between plant- and animal-based ingredients revealed different chemical responses: plant-based foods tend to absorb more oil, while animal-based foods are more prone to lipid oxidation and protein denaturation. Vacuum frying technology has been proven to minimize nutrient degradation and extend oil usability, although its application remains limited in small-scale industries. This study highlights the importance of selecting appropriate frying techniques to preserve nutritional content and food safety, and recommends further comparative research on conventional and innovative frying methods for various types of traditional Indonesian foods.